Licenční smlouvy ve vztahu k ochranným známkám - Šulcová, Jindřiška (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2011)
The rigorous work in the first part deals with theoretical grounds of license agreements issue, the second special part contains interpretation of individual provisions of a license agreement, attention is paid to related issues, such as specifics of contracts with international element, effectiveness of a license agreement to third parties, competition aspects related to license agreement to trademarks and related contractual types. Annex contains sample license agreement in Czech, English and German, franchising agreement and merchandising agreement in Czech.